Pengaruh Intensitas Mengakses Video Pembelajaran IPS di Youtube Terhadap Minat Baca Buku IPS - Ningtias, Widya Asmi; Sujarwo, Sujarwo (Edukasi IPS, 2021)
This study aims to determine whether the intensity of the use of social studies learning videos on YouTube has an effect on interest in reading social studies books for class IX students at SMPN 20 Jakarta. This type of research is quantitative with a survey method through a questionnaire and using a Likert scale. The sample in the study amounted to 81 students using the non-probability sampling method with purposive sampling technique as the sample determination. Hypothesis testing was carried out with the help of SPSS Statistic 26. Based on the testing of data analysis requirements and hypothesis testing that had been carried out, the T test value was 12.451> 1.99, meaning that H1 was accepted which "there is" the effect of the intensity of accessing social studies learning videos on YouTube on reading interest Social Studies book for class IX students at SMPN 20 Jakarta. The regression model Y = 54.043 + 0.446X shows that variable X has a positive effect on variable Y. The intensity of the use of social studies learning videos on YouTube affects interest in reading social studies books by 66.2%, while the rest is influenced by other variables not examined.     Abstrak Penelitian ini bertujuan untuk mengetahui apakah intensitas pemanfaatan video pembelajaran IPS di YouTube berpengaruh terhadap minat baca buku IPS siswa kelas IX di SMPN 20 Jakarta. Jenis penelitian ini adalah kuantitatif dengan metode survei melalui koesioner dan menggunakan skala likert. Sampel dalam penelitian berjumlah 81 siswa dengan menggunakan metode non-probability sampling dengan teknik purposive sampling sebagai penentuan sampelnya. Pengujian hipotesis dilakukan dengan bantuan SPSS Statistic 26. Berdasarkan pengujian persyaratan analisis data dan pengujian hipotesis yang telah dilakukan, dihasilkan nilai uji T 12,451>1,99, artinya H1 diterima yang mana “terdapat” pengaruh intensitas mengakses video pembelajaran IPS di YouTube terhadap minat baca buku IPS siswa kelas IX di SMPN 20 Jakarta. Model regresi Y = 54,043 + 0,446X menunjukkan bahwa variabel X berpengaruh positif terhadap variabel Y. Intensitas pemanfaatan video pembelajaran IPS di YouTube mempengaruhi minat baca buku IPS sebesar 66,2%, sedangkan sisanya dipengaruhi oleh variabel lain yang tidak diteliti.